PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 12 TENGGANAU - Sulastri, Sulastri; Kartini, Kartini; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research aims to improve the learning process and improve mathematics learning outcomes in fourth grade students of SD Negeri 12 Tenganau by implementing STAD cooperative learning model. The subjects were 26 students consisting of 12 male and 16 female who have the heterogeneous academic asbility. This research is a class act with two cycles. Each cycle consisted of three meetings and one at each end of the cycle UH and it has four stages, namely planning, implementation, observation with reflection. The results based on the sheet observations of teachers and students activity have done well after the action. An increase in the number of students who achieved the KKM in UH in the end of each cycle compare to the number of students who achieve a score of KKM on basic score. The results of this study indicate that the application of STAD cooperative learning model can improve the process of learning mathematics and improve learning outcomes in fourth grade students of SD Negeri 12 Tenganau in the odd semester in academic year 2013/2014.Key words: learning process, learning outcomes Mathematics, Cooperative Learning, STAD, classroom action research.